ANALYSIS OF CIVIL SERVANT’S UNDERSTANDING OF BALLAST WATER MANAGEMENT CONVENTIONS (FSTPT Indonesia, 2023)
Ballast water is water used by ships to maintain balance when the ship is unloaded. Ballast water is known to contain microorganisms that are detrimental to human health and the environment, as well as economic losses. IMO enacted the Ballast Water Management Convention to regulate the management of ballast water before it is discharged into the sea, as an effort to prevent the spread of microorganisms into the environment. This study aims to determine the understanding of civil servant in the shipping sector. The research method is an analytic description with a cross sectional approach using questionnaires and in-depth interviews. The results show that most of the respondents do not understand the provisions of BWM correctly. Many incorrect statements, ignorance and forget about the rules of BWM with a high percentage value. Our suggestion is to socialize the BWM Convention to civil servant in the shipping sector or maritime as a provision in carrying out work through training, seminars and workshops. ABSTRAKAir ballast adalah air yang digunakan kapal untuk menjaga keseimbangan ketika kapal tanpa muatan. Air ballast diketahui mengandung mikroorganisme yang merugikan bagi kesehatan dan lingkungan, serta kerugian secara ekonomis. IMO memberlakukan Ballast Water Management Convention untuk mengatur pengelolaan air ballast sebelum dibuang ke laut, sebagai upaya untuk mencegah tersebarnya mikroorganisme ke dalam lingkungan. Penelitian ini bertujuan untuk mengetahui pemahaman ASN (Aparatur Sipil Negara) sektor pelayaran sebagai pengajar, marine inspektor, Perwira di kapal negara dan Pandu terhadap ketentuan BWM Convention. Metode penelitian adalah deskripsi analitik dengan pendekatan cross sectional menggunakan kuesioner dan wawancara mendalam. Dari hasil menunjukkan bahwa sebagian besar responden belum memahami ketentuan BWM secara benar. Banyak pernyataan yang salah, tidak tahu dan lupa tentang aturan BWM dengan nilai persentase yang tinggi. Saran kami adalah sosialisasi tentang BWM Convention kepada ASN sektor pelayaran sebagai bekal dalam melaksanakan pekerjaan melalui diklat, seminar maupun workshop.